Barriers in recognising, diagnosing and managing depressive and anxiety disorders as experienced by Family Physicians; a focus group study - Zitman Frans; van de Lisdonk Eloy; van Hout Hein; van Rijswijk Eric; van Weel Chris (BMC Family Practice, 2009)
Abstract Background The recognition and treatment of depressive- and anxiety disorders is not always in line with current standards. The results of programs to improve the quality of care, are not encouraging. Perhaps these programs do not match with the problems experienced in family practice. This study aims to systematically explore how FPs perceive recognition, diagnosis and management of depressive and anxiety disorders. Methods focus group discussions with FPs, qualitative analysis of transcriptions using thematic coding. Results The FPs considered recognising, diagnosing and managing depressive- and anxiety disorders as an important task. They expressed serious doubts about the validity and usefulness of the DSM IV concept of depressive and anxiety disorders in family practice especially because of the high frequency of swift natural recovery. An important barrier was that many patients have difficulties in accepting the diagnosis and treatment with antidepressant drugs. FPs lacked guidance in the assessment of patients' burden. The FPs experienced they had too little time for patient education and counseling. The under capacity of specialised mental health care and its minimal collaboration with FPs were experienced as problematic. Valuable suggestions for solving the problems encountered were made Conclusion Next to serious doubts regarding the diagnostic concept of depressive- and anxiety disorders a number of factors were identified which serve as barriers for suitablemental health care by FPs. These doubts and barriers should be taken into account in future research and in the design of interventions to improve mental health care in family practice.